Repetition priming in mild cognitive impairment and mild dementia: Impact of educational attainment. Issue 4 (21st April 2018) - O'Shea, Deirdre M.; De Wit, Liselotte; Yutsis, Maya; Castro, Melissa; Smith, Glenn E.
ABSTRACT: Objective : To examine the role of education on repetition priming performances in healthy aging, mild cognitive impairment (MCI), and mild dementia. Method : A total of 72 participants (healthy = 27, with MCI = 28, with mild dementia = 17) took part in the present study. Priming was assessed using the Word Stem Completion Test, and delayed and recognition memory was assessed using the Rey Auditory Verbal Learning Test. A multinomial regression analysis was used to examine whether years of education moderated priming and declarative memory performances in predicting group membership. Results : Priming performances discriminated between individuals with MCI and mild dementia but not between MCI and healthy. Additionally, this effect was most salient in individuals with low levels of education. Education did not moderate explicit memory performances in predicting group membership. Conclusion : Little is known about the impact of education on priming in verbal memory. Our findings indicate that formal years of education impact priming performances in MCI and individuals with mild dementia, which may have implications for designing interventions targeting "intact" cognitive abilities in these groups.